Analysis Conditions Basketball Referee Riau (AWABRI) - Oki Candra; Dupri Dupri; Nesha Putri Irshanty (IKIP Budi Utomo Malang, 2020)
The purpose of this study was to determine the extent of the condition of Riau basketball referees. This research is descriptive with a quantitative approach. The population in the study was Riau basketball referee (AWABRI), amounting to 12 people. The sampling technique in this study is this purposive sampling where the referee taken is the referee who is active in leading the match. The results of research conducted on the son referee, the physical condition of Riau putera basketball referee with an average score of 8.3 by percentage 90%, so the physical condition category of Riau son referee basketball is included in the medium category. Whereas for Riau women's basketball referees with a score of 10 by percentage 50%, the physical condition of Riau women's basketball referees is included in the Good category.